Electromagnetic shielding composite material and preparation method thereof

By using a combination of thermoplastic polyamide resin, polyester liquid crystal, carbon fiber conductive filler and thermosetting resin binder in the electromagnetic shielding composite material, the problem of degradation in the performance of existing materials when used in high temperature and humid and heat environments is solved, and the electromagnetic shielding effect with low water absorption, good processability and strong heat conduction is achieved.

CN119798987APending Publication Date: 2025-04-11JIANGSU AOSHENG COMPOSITE MATERIALS HI TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510025317.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-06
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

When used in high temperature and humid environments, existing electromagnetic shielding composite materials have problems such as difficulty in improving the conductivity effect, poor water absorption and warping performance, resulting in a decline in the overall performance of the material.

Method used

The combination of thermoplastic polyamide resin, polyester liquid crystal, carbon fiber conductive filler and thermosetting resin binder is used to determine the melting point of the polyamide resin through a differential scanning calorimeter test, and the carbon fiber and porous metal are uniformly mixed with high-speed ball mill to improve the dispersion and bonding strength of the material.

Benefits of technology

It realizes the low water absorption rate, good processability, strong thermal conductivity and electromagnetic shielding energy efficiency of electromagnetic shielding composite materials, and improves the overall performance and service life of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005232998420000061
    Figure BDA0005232998420000061
  • Figure BDA0005232998420000062
    Figure BDA0005232998420000062
  • Figure BDA0005232998420000071
    Figure BDA0005232998420000071
Patent Text Reader

Abstract

The invention relates to an electromagnetic shielding composite material and a preparation method thereof, and the electromagnetic shielding composite material comprises the following raw materials in parts by weight: 100 parts of thermoplastic polyamide resin, 10-20 parts of polyester liquid crystal, 10-20 parts of carbon fiber conductive filler and 10-20 parts of thermosetting resin binder. 3 to 20 parts of polyester liquid crystal; 30-80 parts of a carbon fiber conductive filler; 3 to 20 parts of a thermosetting resin binder; wherein the thermoplastic polyamide resin comprises first polyamide resin and second polyamide resin, and the melting point of the first polyamide resin is higher than that of the second polyamide resin. The electromagnetic shielding composite material provided by the invention is suitable for various electronic elements, and the electromagnetic shielding composite material is low in water absorption rate, high in machinability and high in heat conduction and electromagnetic shielding energy efficiency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of preparation of electromagnetic shielding composite materials, and in particular relates to an electromagnetic shielding composite material and a preparation method thereof. Background Art

[0002] With the increase of Internet devices, the energy density of electromagnetic waves in the environment is increasing year by year, and electromagnetic radiation not only interferes with and damages the normal operation of other electronic devices, reduces the reliability and stability of the equipment, but also affects people's daily life and health. Therefore, the research and application of electromagnetic shielding materials has become a research topic that the industry pays more and more attention to.

[0003] Compared with traditional metal electromagnetic shielding materials, thermoplastic electromagnetic shielding composite materials have the advantages of good processing performance, light weight and high strength, corrosion resistance, recyclability and adjustable shielding effectiveness, and are considered to be new electromagnetic shielding materials with broad application prospects. Since some electronic instruments and equipment are used in high temperature and humid environments for a long time, electromagnetic shielding materials are required to have not only good magnetic field shielding effects, but also good temperature adaptability and waterproofness.

[0004] Patent CN109504076A discloses an electromagnetic shielding polyamide material, which is composed of the following raw materials in parts by weight: 75-85 parts of polyamide resin; 3-5 parts of PEDOT-g-MAH:PSS conductive powder; 10-15 parts of carbon fiber; 0.5-2 parts of silane coupling agent; 0.1-0.5 parts of antioxidant; and 2-3 parts of other additives. The addition of conductive powder and a large amount of carbon fiber has poor dispersion uniformity in the system, which not only affects the improvement of the conductive effect, but also is not conducive to improving the water absorption and warping properties. After absorbing water for a long time, the overall performance of the material decreases.

[0005] Patent CN102985492A uses aromatic polyamide as the base resin to prepare electromagnetic shielding material. Aromatic polyamide has low water absorption and strong rigidity. It is compounded with a large amount of carbon fiber and metal powder. The resin material has poor fluidity during the preparation process and is difficult to process. In addition, carbon fiber, metal powder and polyamide have strong rigidity, poor interaction and strong interface effect, resulting in poor bonding, electromagnetic shielding performance and poor thermal conductivity. Summary of the invention

[0006] The object of the present invention is to provide an improved electromagnetic shielding composite material, which is suitable for various electronic components and has low water absorption, strong processability, and strong thermal conductivity and electromagnetic shielding efficiency.

[0007] The present invention also provides a method for preparing the electromagnetic shielding composite material.

[0008] In order to achieve the above object, a technical solution adopted by the present invention is:

[0009] An electromagnetic shielding composite material, the raw materials of which include thermoplastic polyamide resin, polyester liquid crystal, carbon fiber conductive filler, and thermosetting resin binder, wherein the raw materials are:

[0010] Thermoplastic polyamide resin: 100 parts;

[0011] Polyester liquid crystal: 3-20 parts;

[0012] Carbon fiber conductive filler: 30-80 parts;

[0013] Thermosetting resin binder: 3-20 parts;

[0014] Wherein, the thermoplastic polyamide resin includes a first polyamide resin and a second polyamide resin, and the melting point of the first polyamide resin is higher than the melting point of the second polyamide resin.

[0015] In some preferred embodiments of the present invention, the thermoplastic polyamide resin has -CONH- in its main chain.

[0016] According to some specific aspects of the present invention, the thermoplastic polyamide resin is a combination of one or more selected from aliphatic polyamide, semi-aromatic polyamide, and aromatic polyamide.

[0017] According to some specific aspects of the present invention, the aliphatic polyamide is a combination of one or more selected from polybutylene adipamide, polyhexamethylene adipamide, polycaprolactam, polyhexamethylene sebacamide, polydodecane diamide, and polydecane diamide;

[0018] According to some specific aspects of the present invention, the semi-aromatic polyamide is a combination of one or more selected from polybutylene terephthalamide, polybutylene furan diamine, polypentamethylene terephthalamide, polypentamethylene furan diamine, polyhexamethylene terephthalamide, polyhexamethylene furan diamine, polynonamethylene terephthalamide, polynonamethylene furan diamine, polydecamethylene terephthalamide, polydecamethylene furan diamine, polydodecamethylene terephthalamide, polydodecamethylene furan diamine, polytridecaproamide, polytridecaproamide, polyhexamethylene terephthalamide decanediamine, polyfuran dicarboxamide decanediamine, polypentamethylene terephthalate, and polyfuran dicarboxamide decanediamine.

[0019] According to some specific aspects of the present invention, the aromatic polyamide is a combination of one or more selected from poly(p-phenylene terephthalamide), poly(p-phenylene furan dicarboxamide), and poly(p-phenylene terephthalate furan dicarboxamide).

[0020] In some preferred embodiments of the present invention, the melting point of the first polyamide resin is 250-350°C, and the melting point of the second polyamide resin is 100-250°C.

[0021] The melting points of the first polyamide resin and the second polyamide resin were tested by differential scanning calorimetry. The polyamide resins were quantitatively weighed, pressed into an aluminum crucible, and placed in the tester. The temperature was raised under the protection of N2 gas flow at a rate of 5°C / min. The temperature was raised from room temperature to 350°C, maintained for 5 minutes, and then cooled to room temperature at a rate of 10°C / min, followed by a second heating at 5°C / min. The temperature corresponding to the peak value of the melting peak during the second heating process was the melting point of the product.

[0022] According to some preferred and specific aspects of the present invention, the melting point of the first polyamide resin is preferably 290-340°C, the melting point of the second polyamide resin is 200-230°C, and the polyamide resin has good processing fluidity and water absorption.

[0023] According to some specific aspects of the present invention, the mass percentage of the first polyamide resin is 80-97%, and the mass percentage of the second polyamide resin is 3-20%. If the content of the first polyamide resin is too much, it is easy to cause poor fluidity and cause processing difficulties; if the content of the first polyamide resin is too little, the polyamide resin end groups are more exposed, easy to absorb water and degrade, and the service life is shortened.

[0024] According to some preferred and specific aspects of the present invention, the mass percentage of the first polyamide resin is 80-95%, and the mass percentage of the second polyamide resin is 5-20%.

[0025] According to some preferred and specific aspects of the present invention, the mass percentage of the first polyamide resin is 85-95%, and the mass percentage of the second polyamide resin is 5-15%.

[0026] In some preferred embodiments of the present invention, the polyester liquid crystal is formed by co-condensation of aromatic hydroxycarboxylic acid, aromatic dibasic acid, dihydric phenol and / or polyethylene terephthalate, diethylene terephthalate.

[0027] The raw materials of the polyester liquid crystal include aromatic hydroxycarboxylic acid, aromatic dibasic acid, dihydric phenol and polyethylene terephthalate, which are co-condensed to form polyester liquid crystal.

[0028] Polyester liquid crystal is an aromatic polyester liquid crystal with thermotropic liquid crystal properties. During the heating process, it can be transformed from a solid state (crystalline or glassy state) to a liquid crystal polymer at a certain temperature. Polyester liquid crystal has a relatively unique molecular structure and thermal behavior. Its molecules are composed of rigid rod-shaped macromolecular chains. After being heated and melted, it forms a liquid crystal state with both solid and liquid properties. It has the advantages of high strength, high modulus, high chemical corrosion resistance, good dimensional stability, self-flammability constant, etc. It is in an ultra-high fluid state at high temperature, and its dielectric constant is low in the high-frequency state, and it has excellent radiation resistance.

[0029] According to some specific aspects of the present invention, the polyester liquid crystal has a melt viscosity of 5 to 80 Pa·s at 300° C. and a shear rate of 1000 / s, and the melt viscosity is tested according to method ISO 11443.

[0030] According to some preferred and specific aspects of the present invention, the polyester liquid crystal has a melt viscosity of 20 to 50 Pa·s at 300° C., and the composite material has good processing fluidity.

[0031] In some preferred and specific aspects of the present invention, further considering the cost and mechanical properties, the amount of polyester liquid crystal is 8 to 15 parts.

[0032] In some preferred embodiments of the present invention, the raw materials of the carbon fiber conductive filler include porous metal and carbon fiber. The porous metal material has a large number of directional or random holes dispersed inside the metal, which has a small specific gravity, good rigidity and specific strength, good vibration absorption and sound absorption performance, and good permeability and air permeability. The large specific surface area of ​​the porous metal material gives it a strong heat exchange and heat dissipation capacity. Under the synergistic effect of carbon fiber and porous metal, the electromagnetic shielding composite material has better electromagnetic shielding energy efficiency and heat dissipation performance, and can improve the overall mechanical properties of the material.

[0033] According to some specific aspects of the present invention, the porous metal is selected from one or more combinations of iron, cobalt, nickel, copper, zinc, aluminum, titanium, vanadium, chromium, manganese, silver, platinum and gold, and the porous metal is in a foam type, a lotus root type or a honeycomb type.

[0034] According to some preferred and specific aspects of the present invention, the porous metal is selected from one or more of foamed nickel and foamed copper, and the carbon fiber and the porous metal have good cooperation.

[0035] According to some specific aspects of the present invention, the mass percentage of the porous metal is 50-90%, and the mass percentage of the carbon fiber is 10-50%.

[0036] According to some preferred and specific aspects of the present invention, the mass percentage of the porous metal is 60-80%, the mass percentage of the carbon fiber is 20-40%, and the electromagnetic shielding composite material has good electromagnetic shielding energy efficiency and heat dissipation performance.

[0037] According to some specific aspects of the present invention, the average pore size of the porous metal is 10-200 μm. The average pore size is the cross-sectional diameter of the pores in the porous metal material, which is measured by photographing the cross section with a scanning electron microscope.

[0038] According to some preferred and specific aspects of the present invention, the average pore size of the porous metal is preferably 30-180 μm, which is conducive to the embedding of carbon fiber powder into the pores of the porous metal.

[0039] In some preferred embodiments of the present invention, the carbon fiber is a combination of one or more selected from powdered carbon fiber, short fiber carbon fiber, long fiber carbon fiber, carbon fiber filament, and carbon fiber cloth. Carbon fiber material is mainly composed of carbon element, and has light weight, good chemical stability, and excellent electrical conductivity.

[0040] According to some specific aspects of the present invention, the average length of the powdered carbon fiber is 10 to 200 μm.

[0041] According to some preferred and specific aspects of the present invention, in order to better embed into the porous metal, the average length of the powder carbon fiber is preferably 10 to 100 μm.

[0042] In some preferred and specific aspects of the present invention, the amount of the carbon fiber conductive filler is 40 to 70 parts by weight.

[0043] In some preferred embodiments of the present invention, the thermosetting resin binder contains a large number of reactive groups, such as hydroxyl groups, ether bonds, amine bonds, and ester bonds, which facilitate bonding of porous metal and carbon fibers.

[0044] According to some specific aspects of the present invention, the thermosetting resin binder is a combination of one or more selected from epoxy resin binder, unsaturated polyester resin binder, phenolic resin binder, urea-formaldehyde resin binder, and melamine-formaldehyde resin binder.

[0045] In some preferred and specific aspects of the present invention, epoxy resin adhesive is preferred in view of reactive group content and adhesive properties.

[0046] In some preferred and specific aspects of the present invention, considering the bonding strength, the amount of the thermosetting resin binder is 5 to 15 parts.

[0047] Another technical solution provided by the present invention is:

[0048] A method for preparing the above electromagnetic shielding composite material, the preparation method comprising:

[0049] (1) Preparing thermoplastic polyamide resin and carbon fiber conductive filler;

[0050] (2) Firstly, a thermosetting resin binder and a carbon fiber conductive filler are mixed to form a mixture, and then the mixture, a liquid crystal polyester and a thermoplastic polyamide resin are melt-mixed, and then molded to obtain the electromagnetic shielding composite material.

[0051] According to some specific aspects of the present invention, in step (1), when preparing a thermoplastic polyamide resin: the first polyamide resin and the second polyamide resin are weighed in proportion and melt-mixed to obtain a thermoplastic polyamide resin; when preparing a carbon fiber conductive filler: the porous metal and carbon fiber are weighed in proportion and placed in a high-speed ball mill and stirred and mixed evenly to obtain a thermoplastic polyamide resin.

[0052] According to some specific aspects of the present invention, in step (2), the thermosetting resin binder and the carbon fiber conductive filler are first mixed to form a mixture, and then the mixture is preheated and blended with the liquid crystal polyester at a first temperature, and then the thermoplastic polyamide resin is added, and the temperature is raised to a second temperature for melt mixing, wherein the first temperature ranges from 150 to 250° C., and the second temperature ranges from 280 to 390° C. The advantage is that the functional groups of the polyester liquid crystal can first be better bonded to the carbon fiber conductive filler, and then the polyester liquid crystal is bonded to the polyamide, and thus the bonding is sequentially performed to improve the bonding strength.

[0053] In some preferred and specific aspects of the present invention, the first temperature is 150-200°C, and the second temperature is 280-320°C.

[0054] According to some specific aspects of the present invention, in step (2), the molding process refers to molding into a certain shape by molding, extrusion, or injection molding.

[0055] Due to the application of the above technical solution, the present invention has the following advantages compared with the prior art:

[0056] The electromagnetic shielding composite material provided by the present invention uses the first polyamide resin as the main substrate, has strong acid and alkali resistance, excellent mechanical properties, and low water absorption, which gives it a long service life; the first polyamide resin, the second polyamide resin and the liquid crystal polyester are compounded and have better high-temperature fluidity, thereby having better processability; no solvent is used in the preparation process, which is environmentally friendly and has a simple preparation process; carbon fiber conductive filler is used, among which the porous metal has a large specific surface area and better wave absorption and heat dissipation performance, which enhances the electromagnetic shielding effectiveness and cooperates with the carbon fiber to quickly dissipate the heat energy generated by absorbing too much electromagnetic waves, thereby avoiding overheating of electronic components. DETAILED DESCRIPTION

[0057] The present invention is further described below in conjunction with the illustrated embodiments.

[0058] The raw materials of Examples 1-15 and Comparative Examples 1-5 are as follows.

[0059]

Thermoplastic polyamide resin

[0060] A1: 95% by mass of the first polyamide resin PA10T (melting point 315° C.) and 5% by mass of the second polyamide resin PA6 (melting point 216° C.) are blended, the mixture is heated to 320° C., stirred for 30 minutes, and then cooled.

[0061] A2: 80% by mass of the first polyamide resin PA10T (melting point 315° C.) and 20% by mass of the second polyamide resin PA6 (melting point 216° C.) are blended, the mixture is heated to 320° C., stirred for 30 minutes and then cooled.

[0062] A3: 97% by mass of the first polyamide resin PA10T (melting point 315° C.) and 3% by mass of the second polyamide resin PA6 (melting point 216° C.) are blended, the mixture is heated to 320° C., stirred for 30 minutes and then cooled.

[0063] A4: 95% by mass of the first polyamide resin PA6T (melting point 370° C.) and 5% by mass of the second polyamide resin PA66 (melting point 260° C.) are mixed, heated to 375° C., stirred for 30 minutes and then cooled. A5: The first polyamide resin PA10T.

[0064] A6: second polyamide resin PA6.

[0065]

Polyester liquid crystal

[0066] B1: Polyester liquid crystal, R8500 polyester liquid crystal produced by Kingfa Technology Wantong Special Engineering Plastics, with a melt viscosity of 15-20 Pa·s at 300°C and a shear rate of 1000 / s.

[0067] B2: Polyester liquid crystal, R835 polyester liquid crystal produced by Kingfa Technology Wantong Special Engineering Plastics, with a melt viscosity of 40-50 Pa·s at 300°C and a shear rate of 1000 / s.

[0068]

Powdered carbon fiber

[0069] C1: MLD-30, carbon fiber powder produced by Toray Industries, Ltd., Japan, with a fiber length of 30 μm.

[0070] C2: MLD-300, carbon fiber powder produced by Toray Industries, Ltd., Japan, with a fiber length of 130μm.

[0071]

Porous metal materials

[0072] D1: Nickel foam, MF005 nickel foam produced by Changsha Liyuan New Materials Co., Ltd., with an average pore size of 150μm. D2: Copper foam, MF001 copper foam produced by Changsha Liyuan New Materials Co., Ltd., with an average pore size of 110μm.

[0073]

Carbon fiber conductive filler

[0074] Carbon fiber conductive fillers (E1-E5) were prepared by weighing and blending according to the formula shown in Table 1.

[0075] Table 1 Proportions of carbon fiber conductive fillers (E1-E5)

[0076]

[0077]

Thermosetting resin binder

[0078] F: Epoxy resin, YX4000H biphenyl type epoxy resin produced by Mitsubishi Chemical Corporation.

[0079] Examples 1-15 and Comparative Examples 1-5 are provided. See Table 2 for the raw material formulas of Examples 1-15 and Comparative Examples 1-5.

[0080] Table 2 Raw materials of electromagnetic shielding composite materials of Examples 1-15 and Comparative Examples 1-5

[0081]

[0082]

[0083] According to the raw material formula in Table 2, the thermosetting resin binder and the carbon fiber conductive filler are weighed and mixed in a certain amount. The impregnated carbon fiber conductive filler and the liquid crystal polyester are preheated and blended at 200°C for 1 hour. Subsequently, the thermoplastic polyamide resin is added and the temperature is raised to 320°C for melt mixing for 1 hour. Furthermore, the composite material is formed into a certain shape by molding, extrusion and injection molding to obtain an electromagnetic shielding composite material.

[0084] Example 4 According to the raw material formula in Table 2, a certain amount of thermosetting resin binder and carbon fiber conductive filler are weighed, the impregnated carbon fiber conductive filler and liquid crystal polyester are preheated and blended at 200°C for 1 hour, then thermoplastic polyamide resin is added, the temperature is raised to 375°C and melt mixed for 1 hour, and then, it is formed into a certain shape by molding, extrusion, injection molding, etc. to obtain an electromagnetic shielding composite material.

[0085] Comparative Example 6: According to the raw material formula in Table 2, a certain amount of thermosetting resin binder and carbon fiber conductive filler are weighed, the impregnated carbon fiber conductive filler and liquid crystal polyester are preheated and blended at 200°C for 1 hour, then thermoplastic polyamide resin is added, the temperature is raised to 230°C and melt mixed for 1 hour, and then, it is formed into a certain shape by molding, extrusion and injection molding to obtain an electromagnetic shielding composite material.

[0086] The electromagnetic shielding composite materials of Examples 1-15 and Comparative Examples 1-5 were subjected to the following tests. Unless otherwise specified, each test was conducted at 25° C. The main indicators are as follows:

[0087] 1. Average electromagnetic shielding effectiveness: tested in accordance with GB / T30142-2013 standard, the test frequency range is 8~12GHz;

[0088] 2. Tensile strength: Tested according to GB / T 1040.1-2018, the specimen is stretched at a rate of 5 mm / min, and the specimen size is 100 mm × 10 mm × 5 mm;

[0089] 3. Thermal conductivity: Tested in accordance with the national standard GB / T 10297-2015, the sample size is 40mm×80mm×120mm, the thermocouple measurement spacing is 60mm, and the heating power is 2KW / h.

[0090] Table 3 Performance data of electromagnetic shielding composite materials of Examples 1-15 and Comparative Examples 1-5

[0091]

[0092]

[0093] As shown in Tables 2 and 3, compared with the comparative example, the electromagnetic shielding composite material prepared in the embodiment has better thermal conductivity and better electromagnetic shielding effectiveness; the electromagnetic shielding film prepared in the embodiment has excellent mechanical properties, and the preparation process is pollution-free and convenient for large-scale production.

[0094] The main difference between Example 7 and Comparative Example 1 is that Comparative Example 1 does not use polyester liquid crystal, and the results in Table 3 show that the average electromagnetic shielding effectiveness, tensile strength, and thermal conductivity of Example 7 are better than those of Comparative Example 1. The main difference between Example 1 and Comparative Example 2 is that Comparative Example 2 does not use carbon fiber conductive filler, and the results in Table 3 show that the average electromagnetic shielding effectiveness, tensile strength, and thermal conductivity of Example 1 are better than those of Comparative Example 2. The main difference between Example 1 and Comparative Example 3 is that Comparative Example 3 does not use thermosetting resin binder, and the average electromagnetic shielding effectiveness, tensile strength, and thermal conductivity of Example 1 are better than those of Comparative Example 3.

[0095] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.

Claims

1. An electromagnetic shielding composite material, characterized in that: The raw materials of the electromagnetic shielding composite material include thermoplastic polyamide resin, polyester liquid crystal, carbon fiber conductive filler, and thermosetting resin binder. In parts by weight, the raw materials include: Thermoplastic polyamide resin: 100 parts; Polyester liquid crystal: 3-20 parts; Carbon fiber conductive filler: 30-80 parts; Thermosetting resin binder: 3-20 parts; Wherein, the thermoplastic polyamide resin includes a first polyamide resin and a second polyamide resin, and the melting point of the first polyamide resin is higher than the melting point of the second polyamide resin.

2. The electromagnetic shielding composite material according to claim 1, characterized in that: The melting point of the first polyamide resin is 250-350°C, and the melting point of the second polyamide resin is 100-250°C.

3. The electromagnetic shielding composite material according to claim 1, characterized in that: The mass percentage of the first polyamide resin is 80-97%, and the mass percentage of the second polyamide resin is 3-20%.

4. The electromagnetic shielding composite material according to claim 1, characterized in that: The main chain of the thermoplastic polyamide resin has -CONH-; and\or, The thermoplastic polyamide resin is a combination of one or more selected from aliphatic polyamide, semi-aromatic polyamide, and aromatic polyamide; and\or, The aliphatic polyamide is a combination of one or more selected from polybutylene adipamide, polyhexamethylene adipamide, polycaprolactam, polyhexamethylene sebacamide, polyhexamethylene dodecanoyl, and polydecamethylene sebacamide; The semi-aromatic polyamide is selected from the group consisting of polybutylene terephthalamide, polybutylene furan dicarboxylamide, polypentamethylene terephthalamide, polypentamethylene furan dicarboxylamide, polyhexamethylene terephthalamide, polyhexamethylene furan dicarboxylamide, polynonamethylene terephthalamide, polynonamethylene furan dicarboxylamide, polydecamethylene terephthalamide, polydecamethylene furan dicarboxylamide, polydodecamethylene terephthalamide, polydodecamethylene furan dicarboxylamide, polytridecaproamide, polytridecaproamide, polyhexamethylene terephthalamide decanediamine, polyfuran dicarboxylamide decanediamine, polypentamethylene terephthalate, and polyfuran dicarboxylamide decanediamine; The aromatic polyamide is selected from one or more combinations of poly(p-phenylene terephthalamide), poly(p-phenylene furan dicarboxamide), and poly(p-phenylene terephthalate furan dicarboxamide).

5. The electromagnetic shielding composite material according to claim 1, characterized in that: The polyester liquid crystal is an aromatic polyester liquid crystal, and has a melting viscosity of 5 to 80 Pa·s at 300° C. and a shear rate of 1000 / s.

6. The electromagnetic shielding composite material according to claim 1, characterized in that: The raw materials of the carbon fiber conductive filler include porous metal and carbon fiber, the mass percentage of the porous metal is 50-90%, and the mass percentage of the carbon fiber is 10-50%; and\or, the porous metal is a combination of one or more selected from iron, cobalt, nickel, copper, zinc, aluminum, titanium, vanadium, chromium, manganese, silver, platinum, and gold.

7. The electromagnetic shielding composite material according to claim 1, characterized in that: The carbon fiber is a combination of one or more selected from powdered carbon fiber, short fiber carbon fiber, long fiber carbon fiber, carbon fiber filament, and carbon fiber cloth, and / or, the average length of the powdered carbon fiber is 10 to 200 μm.

8. The electromagnetic shielding composite material according to claim 1, characterized in that: The thermosetting resin binder is a combination of one or more selected from epoxy resin binder, unsaturated polyester resin binder, phenolic resin binder, urea-formaldehyde resin binder and melamine-formaldehyde resin binder.

9. A method for preparing the electromagnetic shielding composite material according to any one of claims 1 to 8, characterized in that: The preparation method comprises: (1) Preparing thermoplastic polyamide resin and carbon fiber conductive filler; (2) Firstly, a thermosetting resin binder and a carbon fiber conductive filler are mixed to form a mixture, and then the mixture, a liquid crystal polyester and a thermoplastic polyamide resin are melt-mixed, and then molded to obtain the electromagnetic shielding composite material.

10. The method for preparing the electromagnetic shielding composite material according to claim 9, characterized in that: In step (2), the thermosetting resin binder and the carbon fiber conductive filler are first mixed to form a mixture, and then the mixture is blended with the liquid crystal polyester at a first temperature, and then the thermoplastic polyamide resin is added and the temperature is raised to a second temperature for melt mixing, wherein the first temperature ranges from 150 to 250°C and the second temperature ranges from 280 to 390°C.

Citation Information

Patent Citations

  • High modulus composition for emi shielding and molded articles thereof

    CN102985492A

  • Electromagnetic shielding polyamide material and preparation method thereof

    CN109504076A